Answer:Given below
Step-by-step explanation:
A function is said to be odd if
[tex]F\left ( x\right )=F\left ( -x\right )[/tex]
(a)[tex]F\left ( x\right )=x^3+3x[/tex]
[tex]F\left ( -x\right )=-x^3-3x=-\left ( x^3+3x\right )[/tex]
odd function
(b)[tex]F\left ( x\right )=4sin2x[/tex]
[tex]F\left ( -x\right )=-4sin2x[/tex]
odd function
(c)[tex]F\left ( x\right )=x^2+|x|[/tex]
[tex]F\left ( -x\right )=\left ( -x^2\right )+|-x|=x^2+|x|[/tex]
even function
(d)[tex]F\left ( x\right )=e^x[/tex]
[tex]F\left ( -x\right )=e^{-x}[/tex]
neither odd nor even
(e)[tex]F\left ( x\right )=\frac{1}{x}[/tex]
[tex]F\left ( -x\right )=-\frac{1}{x}[/tex]
odd
(f)[tex]F\left ( x\right )=\frac{1}{2}\left ( e^x+e^{-x}\right )[/tex]
[tex]F\left ( -x\right )=\frac{1}{2}\left ( e^{-x}+e^{x}\right )[/tex]
even function
(g)[tex]F\left ( x\right )=xcosx(h)[/tex]
[tex]F\left ( -x\right )=-xcosx(h)[/tex]
odd function
(h)[tex]F\left ( x\right )=\frac{1}{2}\left ( e^x-e^{-x}\right )[/tex]
[tex]F\left ( -x\right )=\frac{1}{2}\left ( e^{-x}+e^{x}\right )[/tex]
odd function